Anticancer L-Asparaginase and Phytoactive Compounds From Plant Against MDR (Methicillindrug resistant) and Fungal Isolates - Ambreen Aisha; Saba Zahra; Imtiaz M. Tahir; Asim Hussain; Naheed Bano; Alishbah Roobi; Nadia Afsheen; Yasir Saleem (SAGE Publishing, 2022)
L-asparaginase is used in chemotherapy for acute lymphoblastic leukemia and other cancers. L-asparaginase derived from bacterial source triggers immune responses. The current study investigates Solanum nigrum as a novel and latent source of L-asparaginase to minimize immunological reactions. The antitumor activity of SN methanol extract was determined using the potato disc assay. InterPro Chimera and InterPro were used to predict the amino acid sequence of L-asparaginase and its anticancer activity. Purification of the enzyme was carried out to homogeneity of 1.51-fold with a recovery of 61.99%. At optimal conditions of 36.5°C, pH 8.6, and 8.5 g/mL substrate, fruit (crude extract) revealed an L-asparaginase titer of 48.23 U/mL. The molecular weight of the enzyme was calculated to be 32 ± 5 kDa using SDS PAGE. The fruit's total flavonoids and phenolic contents are 0.42 ± .030 g/mL and 94 ± 1.9 mg CAE, respectively. Anti-tumorigenic efficacy was determined to be 66% against Agrobacterium tumefaciens . Additionally, the extract possesses potent antifungal and antibacterial properties. Molecular docking provided the structural motifs and underlying interactions between L-asparaginase, N-acetylglucosamine, murine, and chitin. SN contains high levels of the enzyme L-asparaginase and phytochemicals, making it a potential source of anticancer drugs.